A bloom of Karlodinium australe (Gymnodiniales, Dinophyceae) associated with mass mortality of cage-cultured fishes in West Johor Strait, Malaysia - Hong, Chang Lim; Chui, P.L; Toh, Hii Tan; Nyuk, Fong Kon; Leh, Hie Yek; Kieng, Soon Hii; Sing, Tung Teng; Roziawati, Mohd Razali; Gires, Usup; Mitsunori, Iwataki; Po, T.L (Elsevier Ltd., 2014)
A recent (February 2014) mass mortality of fishes was observed in the cage-farming region of the West Johor Strait of Malaysia, involving over four different species of cultured fishes, numbering ∼50,000 fish. A field investigation at six stations along the West Johor Strait collected water samples and examined for the presence of harmful species. Dead fishes were collected for necropsy. The phytoplankton composition was dominated by a species of Karlodinium, at a considerably high cell concentration (0.31–2.34 × 106 cells l−1), and constituting 68.8–98.6% of the phytoplankton relative abundance at all stations. Detailed morphological assessment by light and scanning electron microscopy revealed that the species was Karlodinium australe de Salas, Bolch and Hallegraeff. This was supported by molecular evidence of the nuclear encoded large subunit ribosomal gene (LSU rDNA) and the second internal transcribed spacer (ITS2) via single-cell PCR. The sequences of LSU rDNA yielded 3.6–4.0% divergence when compared to the sister taxon, K. armiger; and >6.5% when compared to other Karlodinium species. Fish necropsy showed symptoms similar to those affected by karlotoxin ichthyotoxins. This is the first report of a mass mortality of cage-cultured and wild fishes attributed to the unarmored dinoflagellate K. australe.